Expatriate assignments: the "same" job may require different tasks. Issue 2 (19th December 2019) - Martin, Scott; James, Reynold
Abstract : Purpose: Given a specific job, this paper aims to examine if the tasks change when moving from one country to another, and if so, whether such changes are at least partly a function of environmental factors. Design/methodology/approach: A mixed-method approach (surveys and interviews) with professional-level expatriates based in the UAE. Findings: The results indicated that the "same" job often required different tasks depending on the country. Given a matching job between home and host countries, 66 per cent of respondents indicated that the job was different and on average, 20 per cent of the job was perceived to be different. Environmental forces did account for meaningful task differences. Legal and regulatory forces were a particularly important driver of task differences. Practical implications: It is important to consider potential task differences in connection with expatriate assignments. Attending to task differences can have a positive impact on staffing, development and management processes. Originality/value: Given the "same" job, the specific tasks may be different depending on the country.